2022
DOI: 10.1177/00187267221081295
|View full text |Cite
|
Sign up to set email alerts
|

The role of organizational settings in social learning: An ethnographic focus on food-delivery platform work

Abstract: How do organizational settings influence learning mechanisms and their outcomes? Based on a 26-month online and offline ethnography, the article specifically analyses couriers’ learning in the context of food-delivery platform work, marked by the heterogeneity of the working crowd, the gig nature of the job and the digitally mediated, individualized and automated management apparatus. Drawing on social learning theory, and in particular on communities of practice (CoPs), the results of the study unpack how the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 86 publications
(147 reference statements)
0
10
0
Order By: Relevance
“…The organizational psychology literature generally finds competence to be a significant predictor of job satisfaction in the service sector (e.g., Carless, 2004). The lack of connection between self‐competence and job satisfaction in our data might have to do with the stereotype of food‐delivery work as a low‐skilled job with almost no barrier to entry (Le Breton & Galière, 2022). Our finding suggests that platform workers are unlikely to derive satisfaction from performing the delivery tasks efficaciously because the job is deemed low‐end and simple.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The organizational psychology literature generally finds competence to be a significant predictor of job satisfaction in the service sector (e.g., Carless, 2004). The lack of connection between self‐competence and job satisfaction in our data might have to do with the stereotype of food‐delivery work as a low‐skilled job with almost no barrier to entry (Le Breton & Galière, 2022). Our finding suggests that platform workers are unlikely to derive satisfaction from performing the delivery tasks efficaciously because the job is deemed low‐end and simple.…”
Section: Discussionmentioning
confidence: 69%
“…The relatively high frequency of group chats, and the strong negative association between the frequency of group chats and the level of mental strain, highlight the important role of peer communication in the age of workforce atomization. To this end, our work adds to the evidence of digital communication technologies helping platform workers draw mental support from co‐workers (Le Breton & Galière, 2022; Soriano & Cabañes, 2020). Nevertheless, given the constrained political environment and the high‐level job satisfaction observed in our survey, it is difficult to envision any large‐scale labor movement in China that goes beyond everyday resistance and flash‐in‐the‐pan mobilization (C. Liu & Friedman, 2021).…”
Section: Discussionmentioning
confidence: 92%
“…Online communities (A22) can bind a group of workers together as they share experiences; this can also prevent gig workers from feeling isolated and give them a sense of belonging (Posada, 2022), by providing social support such as caring, empathy, and trust (Kwan, 2022). The inter‐worker communication via digital technologies can lead to the development of a sense of “networked solidarity,” where gig workers provide each other with help and support (Le Breton & Galière, 2023). Many workers also find and provide support through social media platforms using, for example, Facebook groups and Reddit subforums (de la Vega et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The negative work experiences of the riders mainly come from their salary and the challenges from communicating with all the restaurants, employer, and customers. Le Breton and Galiere (2022) observed that riders rely on the online peer discussion groups for knowledge sharing, symphonizing and shaping in social learning process. In practice, Sun et al (2021) identified that riders are required to perform duty at fixed schedule and such de-flexibilization is caused by the labor management tactics, technological-driven operations, and cultural normalization of platform dependency.…”
Section: Work Conditionsmentioning
confidence: 99%